International experience of introducing innovative financial instruments for the purpose of increasing the energy efficiency of buildings (Journal of Economic Research & Business Administration, 2019)
Kazakhstan housing sector consumes about 11-13% of the electric power and 40% of made thermal energy (Housing and Utilities, 2017). On the average, residential houses in Kazakhstan consume three times more energy per unit of the area, than in the countries of Northern Europe. High level warmly of losses connected with the wear-and-tear of the equipment, as well as with necessity of execution of repair and update is noted. One of the most important directions in the area of power saving and increaseof power efficiency is research and development of financial mechanisms for ultimate users stimulatingattraction of investments to update of existing buildings for increase of their power efficiency. Not seeingto realization of the complex of legislative initiatives and events, communicating Republic politicsKazakhstan in the area of power efficiency needs further perfecting, including in view of the best internationalexperience. In given article opportunities of increase of power efficiency of buildings are consideredat the expense of application of innovative financial tools enabling to increase the profitability ofcapital investments in given sector and to lower expenses. In connection with that financial tools usedin international practice are presented, analysis of deficiencies and advantages of existing tools is carriedout. Practical importance of research consists in consideration of the most effective innovative financialtools in the area of power saving enabling to raise buildings power efficiency, efficiency of investmentsin given area. Experience of implementation of financial tools and mechanisms stimulate the increase ofpower efficiency of buildings in such countries as Netherlands, France, Italy, Slovakia, Estonia etc.